"I AM ENTHUSIASTIC!": EXPLORING STUDENTS' RESPONSES ON THE ROLEPLAY ASSIGNMENT - Puthut Ardianto; Muhamat Ridho Yuliyanto (Academic Journal PERSPECTIVE: Education, Language, and Literature, 2020)
In communicative language teaching, role play has become one of the most well-known activities among language teachers. In fact, in higher educational context, role play is considered to be a good method to facilitate learners oral proficiency. However, the researchers often found some teachers assign too demanding and unclear role play. In fact, some students complained about the implementation of role play at the department. This research aims at revealing students responses when having role play as their group assignment in English classes. A descriptive qualitative design was employed to obtain the research objectives, namely how role play was implemented in the eyes of students and what responses they gave to its assignment. To gather the data, an interview was conducted to one male participant and two female participants taking the Literary Appreciation course at one English Department of a private Islamic university in Yogyakarta. Based on the interview, nine stages were implemented in assigning role play.They are announcing the assignment; distributing materials for role play; modelling the role play; grouping; distributing roles; giving time to prepare the play; creating a role play;having the performance; and giving feedback. Also, there were six responses from students towards the assignment namely happy; not bored; shocked; entertained; anxious; and enthusiastic.